Infrastructure in a Changing World. Trends and Challenges - Alberto Belladonna (Pubblicazioni ISPI, 2020)
In a world on the brink of a global recession caused by the COVID-19 global pandemic, the infrastructure efforts of today and tomorrow are more crucial than ever. For one, they are an indispensable countercyclical tool to mitigate the negative effects of the economic paralysis. But they also constitute a pivotal component for a country's development, raising its competitiveness in the long term. That is why infrastructure will continue to play a critical role even when the pandemic crisis has been tamed. Rapid demographic growth, increasing urbanization, especially in developing countries, coupled with the ounting challenge posed by climate change, are trends that are not going to disappear with the virus. How to cope with these global, long-term trends? How to finance the increasing need for infrastructure? Which major international actors will take the lead? And what role will technology play in shaping the future of infrastructure?